Characteristics of emotional gaze on threatening faces in children with autism spectrum disorders - Zhang, Yifan; Li, Dandan; Yang, Tingting; Chen, Chuanao; Li, Hong; Zhu, Chunyan (Frontiers in Psychiatry, 2022)
Most evidence suggested that individuals with autism spectrum disorder (ASD) experienced gaze avoidance when looking at the eyes compared to typically developing (TD) individuals. Children with ASD magnified their fears when received threatening stimuli, resulting in a reduced duration of eye contact. Few studies have explored the gaze characteristics of children with ASD by dividing emotional faces into threatening and non-threatening pairs. In addition, although dynamic videos are more helpful in understanding the gaze characteristics of children with ASD, the experimental stimuli for some of the previous studies were still emotional pictures. We explored the viewing of dynamic threatening and non-threatening faces by children with ASD in different areas of interest (AOIs). In this study, 6–10 years old children with and without ASD viewed faces with threatening (fearful and angry) and non-threatening (sad and happy) expressions, respectively, with their eyes movements recorded. The results showed that when confronted with threatening faces, children with ASD, rather than TD, showed substantial eye avoidances, particularly non-specific avoidances in the fixation time on the mouths and significantly less time gazing at the mouths in any emotions, which was not observed for non-threatening faces. No correlations were found between the severity of symptoms and characteristics of gaze at the eyes and mouths in children with ASD. These results further enhance the understanding of the gaze characteristics of children with ASD on threatening and non-threatening faces and possibly provide additional evidence for their social interaction improvements.